Effect of Atropine as Premedication to Prevent Vasovagal Attack in Male Patients Undergoing Spinal Anaesthesia - Ahmed Yasser Raddad; Ahmed Adil Ahmed; Nazzal Jebur Mzaiel (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Spinal anaesthesia (SA) is associated with many complications among which the most common side effects are hypotension and bradycardia, The aim of the current study was to assess the effects of prophylactic atropine in prevention of spinal anaesthesia induced hypotension and bradycardia in male. Aim of the Study: The aim of the current study was to assess the effects of prophylactic atropine in prevention of spinal anaesthesia induced hypotension and bradycardia in male. Method: Seventy (70) patients aged 25-60 years old, they had more than one type of surgery. the patients were monitored by the anaesthesiologist, and we monitored the patient’s vital sign related to the operation period, such as blood pressure, heart rate, body temperature, and oxygen saturation, for patients who received atropine before the operation and patients who received atropine during the operation. Results: There were statistically significant differences in the results of the men who received atropine at the beginning of the operation, while for the people who did not receive atropine at the beginning of the operation, there were values that were not statistically significant in the variables of systolic and diastolic blood pressure and heart rate within 5 minutes of receiving spinal anaesthesia. Conclusion: Prophylactic atropine within 1 min of induction of spinal anaesthesia in male patients undergoing surgery reduce the incidence of hypotension and bradycardia.